TIMELINESS LAPORAN KEUANGAN DI INDONESIA (STUDI EMPIRIS TERHADAP EMITEN BURSA EFEK JAKARTA) - Michell Suharli; Sofyan S. Harahap (Media Riset Akuntansi, Auditing & Informasi, 2008)
This Research examines variables which are predicted influencing timeliness finandal statement in Indonesia. Factors that are predicted influencing timeliness in this research are focused on 4 factors: firm scale, profitability, big 4 worldwide accounting firm , and securities return . This research can examines financial statement of 30 companies are listed Jakarta Stock Exchange for period ended December31, 2002 until December31, 2003. Data is collected from Jakarta Stock Exchange and Indonesia Capital Market Directory 2004. In this research uses two variable that is dependent variable and independent variable. To find out influence independent variable to dependent variable used SPSS. Data analysis uses logistic regression and the result of this research that profitability  and big 4 worldwide accounting fin can give significant influence to timeliness, and while the other factors: fine scale and securities return do not.Keyword: Timeliness, firm scale, profitability, big 4 worldwide accounting fin , securities retum.